Identification of Novel Compound Heterozygous Variants of MMP9 in Fetus With Metaphyseal Anadysplasia Type 2 - Cheng, Lin; Yang, Fan; Chen, Xinlin; Kang, Jiawei; Li, Jiafu; Zhang, Yuanzhen; Liu, Juan; Li, Jin; Ma, Jianhong; Duan, Jie (Frontiers in Genetics, 2022)
Matrix metalloproteinase 9 (MMP9) is an important member of the matrix metalloproteinase family and plays a key role in balancing extracellular matrix proteins. Studies have shown that the homozygous mutations in MMP9 can lead to metaphyseal anadysplasia type 2 (MANDP2, OMIM#613073). The clinical phenotype of this disease is limited and there were only 5 reported cases of MANDP2 associated with homozygous MMP9 mutations from 3 families. In this study, we described a case of a fetus with skeletal system malformation. The main clinical manifestations include the short bilateral femur, absence of right fibula, and curved ipsilateral tibia with short length. Importantly, two novel compound heterozygous variants of the MMP9 gene (NM_004994.3: c.151C>T and c.929del) were found through the trio whole-exome sequencing and Sanger sequencing. This is the first report that identified the compound heterozygous variants of the MMP9 gene associated with metaphyseal dysplasia type 2.